1988
DOI: 10.1084/jem.167.2.632
|View full text |Cite
|
Sign up to set email alerts
|

Migration patterns of dendritic cells in the mouse. Traffic from the blood, and T cell-dependent and -independent entry to lymphoid tissues.

Abstract: Dendritic cells (DC) are critical accessory cells for primary immune responses and they may be important stimulators of transplantation reactions, but little is known of their traffic into the tissues. We have studied the migration of purified splenic DC and T lymphocytes, labeled with 111Indium-tropolone, in syngeneic and allogeneic mice. First we demonstrate that DC can migrate from the blood into some lymphoid and nonlymphoid tissues. Immediately after intravenous administration, radio-labeled DC were seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(77 citation statements)
references
References 32 publications
7
69
1
Order By: Relevance
“…This would explain their finding of fluorochrome-labeled cells in splenic T cell areas after i.v. injection, which is a property characteristic of DC (43). Furthermore, it would be valuable to investigate whether the clonal deletion suggested in their study might be due to the migration of Ag-specific clones out of the spleen (44)or down-regulation of CD8 itself (45).…”
Section: Discussionmentioning
confidence: 99%
“…This would explain their finding of fluorochrome-labeled cells in splenic T cell areas after i.v. injection, which is a property characteristic of DC (43). Furthermore, it would be valuable to investigate whether the clonal deletion suggested in their study might be due to the migration of Ag-specific clones out of the spleen (44)or down-regulation of CD8 itself (45).…”
Section: Discussionmentioning
confidence: 99%
“…44 The LN tropism of murine DCs injected s.c. has also been described previously. [45][46][47] However, after i.v. administration, Kupiec-Weglinski et al 45 reported that freshly isolated murine DCs are only transiently found in the lungs and then migrate primarily to the spleen and liver.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] However, after i.v. administration, Kupiec-Weglinski et al 45 reported that freshly isolated murine DCs are only transiently found in the lungs and then migrate primarily to the spleen and liver. The use of different DC populations, more sensitive and nonimmunogenic DC markers, and long-term studies would be worthwhile to define the in vivo biology of ex vivo-manipulated DCs.…”
Section: Discussionmentioning
confidence: 99%
“…This latter property is considered characteristic of DC in lymphoid tissues [28,32] and is related to the increased expression of cell surface costimulatory molecules [30]. Within lymphoid tissues, DC accumulate in the T cell-dependent regions where they are ideally situated to interact with recirculating T cells [24,33] and select those with specific reactivity for the presented antigens. Examination of the functional capacity of APC isolated from secondary lymphoid tissues has indicated that these 'mature' DC are the most potent stimulators of resting T cells, with a capacity which exceeds that of other APC by up to 1000-fold [32,34].…”
Section: Immunostimulatory Properties and Heterogeneity Of Dendritic mentioning
confidence: 99%